Diary of a fly - Cronin, Doreen; Bliss, Harry, 1964- (New York : Joanna Cotler Books, 2007)
A young fly discovers, day by day, that there is a lot to learn about being an insect, including the dangers of flyswatters and that heroes come in all shapes and sizes.
Keywords: Flies -- Fiction; Diaries -- Fiction